Pharmacotherapy of impulse control disorders: A systematic review. (May 2022) - Tahir, Talha; Wong, Melanie Mitsui; Maaz, Muhammad; Naufal, Roshan; Tahir, Rabia; Naidoo, Yedishtra
Highlights: Fluoxetine and oxcarbazepine may be useful for intermittent explosive disorder. Naltrexone may be helpful in the treatment of kleptomania. Divalproex was not effective for decreasing symptoms of intermittent explosive disorder. Abstract: There are currently no evidence-based treatment recommendations for impulse control disorders, which include intermittent explosive disorder (IED), kleptomania and pyromania. Therefore, this systematic review sought to identify all randomized controlled trials (RCTs) that investigated pharmacological treatments for impulse control disorders, to evaluate their efficacy and tolerability. Searches were conducted within MEDLINE, PsychINFO, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) databases. Eight studies were included, six investigated pharmacotherapies for IED, while two investigated management for kleptomania. For the treatment of IED, oxcarbazepine and fluoxetine were the most efficacious. Importantly, divalproex was not superior to placebo in decreasing IED symptoms and was associated with significant adverse effects. In the treatment of kleptomania, only naltrexone was effective. The existing data suggest that the pharmacological treatment for impulse control disorders is an understudied area of psychiatry. Much of the current research on impulse control disorders focuses on management with anticonvulsants and antidepressants. Further studies conducted on these interventions in this population may yield promising results.